Knowledge and economic progress: The role of social technologies - Thráinn Eggertson (University of Iceland, Institute of Economic Studies (IoES), 2008)
I focus on the independent role of social innovation in economic progress. Modern theory of economic growth and development emphasizes endowments, power, incentives, and physical technology, paying scant attention to knowledge of social systems as a scarce resource. I reverse these procedures by directing the spotlight on social technologies, holding constant other important explanatory variables. First, I add social knowledge to Mokyr's (2002) framework for analyzing useful knowledge and compare knowledge of nature to knowledge of the social game. Second, I examine the relationship between physical and social technologies in production—both in the production of commodities and social systems. Third, I discuss institutional policy—attempts by governments to establish and maintain social systems. I borrow ideas from both rational choice and bounded rationality macroeconomics. Finally, I use the evolution of modern biotechnology in the United States to illustrate the problem of knowledge in institutional policy.
Keywords: 330; Social change; institutional change; knowledge society; Technical progress; endogenous growth model; biotechnology; USA; Sozialer Wandel; Institutioneller Wandel; Wissensgesellschaft; Technischer Fortschritt; Endogenes Wachstumsmodell; Biotechnologie; USA